Cross-Layer Combining of Adaptive Modulation and Truncated ARQ Under Cognitive Radio Resource Requirements - Yuli Yang; Hao Ma; Aissa, S. (IEEE transactions on vehicular technology, 2012)
In addressing the issue of taking full advantage of the shared spectrum under imposed limitations in a cognitive radio (CR) network, we exploit a cross-layer design for the communications of secondary users (SUs), which combines adaptive modulation and coding (AMC) at the physical layer with truncated automatic repeat request (ARQ) protocol at the data link layer. To achieve high spectral efficiency (SE) while maintaining a target packet loss probability (PLP), switching among different transmission modes is performed to match the time-varying propagation conditions pertaining to the secondary link. Herein, by minimizing the SU's packet error rate (PER) with each transmission mode subject to the spectrum-sharing constraints, we obtain the optimal power allocation at the secondary transmitter (ST) and then derive the probability density function (pdf) of the received SNR at the secondary receiver (SR). Based on these statistics, the SU's packet loss rate and average SE are obtained in closed form, considering transmissions over block-fading channels with different distributions. Our results quantify the relation between the performance of a secondary link exploiting the cross-layer-designed adaptive transmission and the interference inflicted on the primary user (PU) in CR networks.